2019
DOI: 10.1089/hgtb.2019.013
|View full text |Cite
|
Sign up to set email alerts
|

TLR9-Activating CpG-B ODN but Not TLR7 Agonists Triggers Antibody Formation to Factor IX in Muscle Gene Transfer

Abstract: Innate immune signals that promote B cell responses in gene transfer are generally ill-defined. In this study, we evaluate the effect of activating endosomal Toll-like receptors 7, 8, and 9 (TLR7, TLR7/8, and TLR9) on antibody formation during muscle-directed gene therapy with adeno-associated virus (AAV) vectors. We examined whether activation of endosomal TLRs, by adenine analog CL264 (TLR7 agonist), imidazolquinolone compound R848 (TLR7/8 agonist), or class B CpG oligodeoxynucleotides ODN1826 (TLR9 agonist)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 67 publications
0
23
0
Order By: Relevance
“…Studies in mice demonstrated a unique ability of TLR9 agonists to activate antibody responses to the transgene product in muscle gene transfer, which occurred through induction of moDC responses that enhance activation of T follicular helper T cells. 73 , 74 Therefore, moDC activation is a driver of T cell responses that promote antibody formation. Complement may also be involved in NAB formation.…”
Section: Main Textmentioning
confidence: 99%
“…Studies in mice demonstrated a unique ability of TLR9 agonists to activate antibody responses to the transgene product in muscle gene transfer, which occurred through induction of moDC responses that enhance activation of T follicular helper T cells. 73 , 74 Therefore, moDC activation is a driver of T cell responses that promote antibody formation. Complement may also be involved in NAB formation.…”
Section: Main Textmentioning
confidence: 99%
“…A recent study found that co-administration of a TLR7 agonist (to mimic dsRNA sensing) along with IM delivery of a ssAAV vector failed to reduce transgene product levels in mice, raising doubts about whether dsRNA sensing is relevant in priming AAV vector and transgene product adaptive immune responses. 17 Thus, the role of dsRNA in the overall innate sensing of AAV vectors remains unclear and requires further study.…”
Section: Innate Recognition Of Aav Vectorsmentioning
confidence: 99%
“…78 The RNA backbone of fitusiran contains chemical modifications (including 2′-deoxy-2′-fluoro, and 2′-O-methyl substitutions in ribonucleotides and undisclosed replacements of phosphodiester linkages between them) that prevent its degradation by nucleases and recognition by Toll-like receptor (TLR)3 and TLR7, which are innate immune receptors sensing double-stranded RNAs. [78][79][80][81] Also, the siRNA is conjugated to triantennary Nacetylgalactosamine (GalNAc), which mediates its uptake by hepatocytes through asialoglycoprotein receptor (ASGPR), abundantly expressed in the liver. 78,82 The antisense strands of siRNAs are stable within the RISC for weeks, so the same siRNA molecule may target multiple transcripts, which produces a durable knockdown, and so therapeutic effect (fitusiran is dosed once monthly in the ongoing trials).…”
Section: Emicizumab: Fviiia In Disguise Of An Antibodymentioning
confidence: 99%